DEVELOPING ESP READING MATERIALS FOR PHARMACY STUDENTS OF SMKF PHARMACAMEDAN - Chantika Amalia Rizki; Neni Afrida Sari Harahap (Universitas Negeri Medan, 2018)
This study deals with the developing of ESP Reading materials for students of vocational school. The objectives of the study are to analyze the reading materials which are appropriately used for pharmacy students and to develop the reading text materials for pharmacy students for relevant materials which are appropriate with to the needs of Pharmacy students. The research was conducted by using Research and Development (R&D) method. The subject of the research was 2017/2018 students of the eleventh grade of class B at SMKF Pharmaca Medan. The number of the students was 33 students. The data of this study was collected by need questionnaire analysis, interview analysis, expert judgment and selective reading text. Need analysis questionnaire was calculated by using percentage to get the information of student’s need before developing ESP Reading materials particularly procedure text. Expert judgment data were calculated by using criteria interval of Expert judgment to know validity of the ESP reading materials which has been developed. The ESP reading material was in the form of reading text and reading skill which consisted of sixteen tasks. After the data analyzed, it was found that the experts’s judgment result was 4.4 which had a very good criteria interval and categorized as relevant.The result of the research to find that the developed ESP Reading material was a very good material to be used in teaching learning.